Examining long-term fuel and land use patterns at Ziyaret Tepe, Türkiye using an integrated analysis of seeds, wood charcoal, and dung spherulites - Lucas Proctor; Alexia Smith; Timothy Matney (Archaeological and Anthropological Sciences, 2024)
This study presents the results of a combined dendrological, macrobotanical, and dung spherulite analysis of flotation samples collected from Bronze Age, Late Assyrian, and post-Assyrian contexts at the site of Ziyaret Tepe, located on the southern bank of the Tigris River in southeastern Anatolia. The results of this study show shifting fuel resource exploitation between pre-urbanized phases of the site (ca. 3000–1600 BCE), the urbanized Late Assyrian occupation (882–611 BCE), and the ruralized post-Assyrian (ca. 611 BCE–1500 CE) re-occupations of the site. During the Late Assyrian period, Ziyaret Tepe is thought to have been the location of the city of Tušhan, an important provincial capital of the Neo-Assyrian empire. Evidence for local deforestation near the Tigris River and expanding reliance on dung fuel use during this period indicate overexploitation of fuel resources as larger populations and extractive imperial economic policies placed heavier pressure on local land use. Qualitative dendrological data provides evidence for the intensification of fuelwood harvesting during this period, while textual evidence documented an expansive program of timbering to the north of the site intended to fuel imperial construction projects in the Assyrian heartland. Following the abandonment of Tušhan and the collapse of the Neo-Assyrian empire, local fuel resource exploitation during subsequent occupations of the site shifted towards the direct management of wood fuel resources and increasing reliance on rural pastoralism.